ANALYSIS AND DESIGN ACCOUNTING INFORMATION SYSTEM OF FUNDING AND FINANCING AT KOPERASI SERBA USAHA SYARIAH BAITUL MAAL WAT TAMWIL BAKTI NURUL HUDA - Malicha Aulia Zatalini; Imam Subaweh (Jurnal Ilmiah Ekonomi Bisnis, 2019)
This research conducted at Kopsyah BMT Bakti Nurul Huda and applied a computerized system of funding and financing activities. The purpose of this research is to find out and analyze how the accounting information system of funding and financing activities have been running, whether the system has been running well and how alternatives system is effectively applied in Kopsyah. The research method used is descriptive analysis method with qualitative data. Data analysis techniques consist of literature study, observation, interview, and documentation. The primary data were collected from interviews, notes, and documents which related to accounting activities, while secondary data consist of organizational structure, job description, documents, forms, and accounting records.The analysis tool consists of system analysis and design system with DFD, ERD, normalization, database, and design input as well as output. The results show that Kopsyah has double positions on Baitulmaal between secretary with accounting and cashier or teller with the head of KUB, on Baitultamwil between the cashier or teller with accounting.Documents and the copies have been made, although there are some documents that do not have copies. Recording and data storage are analyzed with daily cash book, control card and Excel. The researcher proposes to separation positions by adding cashier or teller for Baitulmaal, one accounting and one finance manager.The researcher also proposed to replace membership book from manual to printed form, eliminate the function of some documents in Baitulmaal, such as daily cash book, control card, and letter of application to become member, add documents and copies, such as receipt which consists of two sheets, deposit slip, withdrawal slip, slip of disbursement financing and slip of installment financing consists of three sheets and use computerized system and server as well as data storage with database.